Conjunctival melanoma with pronounced central corneal invasion: One-year relapse free follow-up - Colya N. Englisch; Tim Berger; Fidelis Flockerzi; Max Bofferding; Berthold Seitz (American Journal of Ophthalmology Case Reports)
Purpose: Conjunctival melanoma with large corneal involvement is a rarity. We here present a case of conjunctival melanoma with pronounced central corneal involvement. Observation: A 69-year-old fair white male presented with a visual axis impeding corneal nodular lesion with associated conjunctival melanosis. Tumor excision with intraoperative mitomycin c (0.02 %) application for 180 seconds and amniotic membrane transplantation for defect coverage was performed in retrobulbar anesthesia. Histopathological evaluation revealed the nodular lesion to be a conjunctival melanoma (pT1a) with associated conjunctival melanocytic intraepithelial lesion (C-MIL). Conclusion and importance: Most conjunctival melanomas with corneal affection reach a radial corneal involvement of 1 mm. The here reported case accounted for 4 mm, which is seldom and therefore an important report. Surgical excision followed by intraoperative and postoperative mitomycin c exposure was a successful primary treatment. Currently there are no signs of tumor relapse in any part of the eye or the organism 12 months after excision. However, the long-term follow-up needs to be awaited.